Táticas de manejo do tripes do prateamento enneothrips flavens moulton em cultura de amendoim - Rosa, Matheus Elache [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The peanut, Arachis hypogaea L., is a growing crop in Brazil and its current production is about 340 thousand tons, cultivated on an area of 102,3 thousand hectares. However, the yield is limited by the occurrence of pests and diseases and chemical control increases the cost of production. Among the various pests that attack the crop, the most important in Brazil is the silvering thrips Enneothrips flavens Moulton (Thysanoptera: Thripidae). The study aimed to evaluate, under field conditions, management tactics of silvering thrips E. flavens in peanut cultivar of creeping growth; phases of susceptibility peanut creeping growth habit of attack the silvering thrips E. flavens and its effects on productivity; and the effects of potassium fertilization on the population of the silvering thrips E. flavens cultured peanut creeping habit of growth. The three experiments installed in the agricultural years 2012/ 2013 were conducted in Fazenda de Ensino, Pesquisa e Extensão da Faculdade de Engenharia de Ilha Solteira-FE/UNESP, located in Selvíria, MS. In the first experiment was evaluated as management tactics, seed treatment; seed treatment + foliar spraying with 20%, 30% and 40% leaflets in the presence of at least one thrips, respectively; The method of producer (conventional) in the form of seed treatment insecticide + foliar sprays at 30, 45, 60, 75, 90 and 105 days after emergence of the plants; foliar spray insecticide with 30% of the leaflets with the presence of at least 1 and thrips, and control (lack of control). In the second experiment we assessed protection periods of the plants at 10-20 days; 10-30 days; 10-40 days; 10-50 days; 10-60 days; 10-70 days; 10-80 days; 10-90 days; 10-100 days; 20-100 days; 30-100 days; 40-100 days; 50-100 days; 60-100 days; 70-100 days after emergence; and control (lack of control), to characterize the phases of increased susceptibility of peanut, the creeping ...

O amendoim, Arachis hypogaea L., é uma cultura em crescimento no Brasil e a sua produção atual é de cerca de 340 mil toneladas, cultivado em uma área de 102,3 mil hectares. Entretanto, a rentabilidade é limitada pela ocorrência de pragas e doenças e o controle químico eleva o custo de produção. Entre as diversas pragas que atacam a cultura, a mais importante no Brasil é o tripes do prateamento Enneothrips flavens Moulton (Thysanoptera: Thripidae). O trabalho teve por objetivos avaliar, em condições de campo, táticas de manejo do tripes do prateamento E. flavens em cultivar de amendoim de crescimento rasteiro; as fases de suscetibilidade do amendoim de hábito de crescimento rasteiro ao ataque do tripes do prateamento E. flavens e seus reflexos na produtividade; e os efeitos da adubação potássica sobre a população do tripes do prateamento E. flavens em cultura de amendoim de hábito de crescimento rasteiro. Os três experimentos, instalados nos anos agrícolas 2012 e 2013, foram conduzidos na Fazenda de Ensino, Pesquisa e Extensão da Faculdade de Engenharia de Ilha Solteira-FE/UNESP, localizada no município de Selvíria, MS. No primeiro experimento foi avaliado, como táticas de manejo, o tratamento de sementes; tratamento de sementes + pulverização foliar com 20%, 30% e 40% dos folíolos com a presença de pelo menos 1 tripes, respectivamente; o método do produtor (convencional), na forma de tratamento de sementes + pulverizações foliares com inseticida, aos 30, 45, 60, 75, 90 e 105 dias após emergência das plantas; pulverização foliar com inseticida com 30% dos folíolos com a presença de pelo menos 1 tripes e a testemunha (ausência de controle). No segundo experimento avaliou-se os períodos de proteção das plantas aos 10-20 dias; 10-30 dias; 10-40 dias; 10-50 dias; 10-60 dias; 10-70 dias; 10-80 dias; 10-90 dias; 10-100 dias; 20-100 dias; 30-100 dias; 40-100 dias; 50-100 ...
Keywords: Amendoim - Cultivo; Pragas - Controle integrado; Pragas agricolas - Controle integrado; Insects